The Effect of Intellectual Capital and Investment Decisions on Firm Value Through Profitability as an Intervening Variable - Kautsar Adam; Acong Dewantoro Marsono (Jurnal Indonesia Sosial Sains, 2026)
A company's value is an important indicator that reflects investors' perceptions of the company's future performance and prospects. In the era of the knowledge-based economy, intellectual capital and investment decisions are strategic factors believed to increase company value, both directly and indirectly through profitability. This research aims to analyze the influence of intellectual capital and investment decisions on company value with profitability as an intervening variable. This study uses a quantitative approach with an explanatory method. The data used are secondary data in the form of financial statements of companies listed on the Indonesia Stock Exchange during the research period. The data analysis technique was carried out using path analysis to test the direct and indirect influences between variables. The results of the study showed that intellectual capital and investment decisions had a positive and significant effect on profitability. Furthermore, profitability was proven to have a positive and significant effect on company value. In addition, profitability was able to mediate the influence of intellectual capital and investment decisions on company value. These findings confirm the importance of proper management of intellectual assets and investment policies in increasing profitability and value in a sustainable manner.